ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA INDUSTRI ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Sandy Mauk, Sarlince (Jurnal Manajemen Bisnis Dan Organisasi, 2023)
The tobacco processing industry has an important role in driving the national economy. Many companies engaged in the cigarette industry are developing their production, so they are required to increase the quality and quantity of their production. In addition, in the current economic conditions there is competition in various business fields. These conditions require cigarette companies to be able to survive in the competition, companies are required to gain a wider market share, but be able to utilize capital goods efficiently. This study discusses the financial performance assessment of the cigarette industry listed on the Indonesia Stock Exchange for the 2017-2021 period. The results showed that the financial condition of the cigarette company groups listed on the Indonesia Stock Exchange varied greatly in terms of liquidity ratios, solvency ratios, and profitability ratios. If the ranking of good and healthy financial performance is carried out in the cigarette industry, PT. The second Handjaya Mandala Sampoerna, Tbk is PT. Wismilak Tbk then followed by PT. Gudang Garam Tbk and the last one is PT. Bentoel International Investama, Tbk.